L`expérience subjective en sport : éclairage psychophénoménologique de l`attention - Mouchet, A. (Movement & Sport Sciences - Science & Motricité, 2013)
This article aims to present the scientific interest of the psychophenomenology theory and elicitation interview associated with it, to understand the attention of athletes in competition. Considering attention as a modulation of consciousness, with a complex structure and attentional dynamic, we highlight an original framework for studying the activity of the participants within usual context of practice. Moreover we emphasize the link between this theoretical background with a relevant and rigorous methodology, which promotes access to the person`s point of view for understanding the organization of his/her actions. This approach is illustrated through the study of attentional processes of expert rugby players in complex and evolving game-plays. The results serve to emphasize for ball carrier, the singular construction of a configuration of significant cues, as well as the subjective aspect of the attentional dynamics. More generally, we highlight the usefulness of this approach for characterizing the subjective experience of participants, while pointing complementarity with the most usual studies about visual attention. In addition, this paper presents a utility for analyzing and transforming activity of practitioners, coaches or teachers involved in sports or Physical Education.